THE EFFECT OF GIVING BIT JUICE (Beta vulgaris L.) ON SPERMATOZOA MORPHOLOGY OF WISTAR RATS THAT EXPOSED MOSQUITO COIL SMOKE - Septian, Kevin; Ariani, RR Mahayu Dewi; Hermawati, Donna; Nugroho, Trilaksana (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Background : Spermatozoa have a limited amount of antioxidants that cause spermatozoa to be susceptible to oxidative stress by reactive oxygen species (ROS). Mosquito repellent contains the active ingredient Pyrethroid which is one example of external factors that cause DNA damage through oxidative stress. This results in the emergence of secondary metabolites that can act as free radicals, then these free radicals follow the circulation of blood throughout the body including the testes which will cause the process of spermatogenesis to be disrupted and will ultimately affect the quality of the spermatozoa produced. Objective :  To find out the effect of giving beetroot juice (Beta vulgaris) on the morphology of spermatozoa of male Wistar rats that exposed to mosquito coil smoke. Method : This study uses an experimental study, with the type of research design is post test only control group design. The population used in this study were male Wistar rats (Rattus novergicus). The research sample was selected by simple random sampling. Analysis of the data used in the study is an analysis with one way anova test. Results : The mean morphological morphology of normal spermatozoa are: Group K (-) = 96.40; Group K (+) = 88,40; P1 group = 90.80; P2 group = 94.40. One Way ANOVA test found significant differences between the five treatment groups. Post-Hoc Test found significant differences between K (-) with K (+), K (+) with P2, P1 with P2, P1 with K (-). While in the other groups, there was no significant difference in the morphological percentage of spermatozoa. Conclusion : The giving of beet juice can affect sperm morphology Wistar rats that exposed to mosquito coil smoke.Keywords : spermatozoa, bit juice, antioxidant, free radical